The effectiveness of PDT in the correction of inflammatory changes in periodontal tissues according to the experimental studies (Эндодонтия Today)
In an experimental study the possibility of correction of inflammatory periodontal diseases by using such medications as Photoditazin gel 0.5%, Toluidine blue 1% solution, 1% solution of methylene blue, when using a laser that has the wavelength λ = 662 nm and a power of 100 j/cm2 had been explored on experimental genetic model of 20 mice BRSUNT.